The Implementation of STEM Project-Based Learning and Critical Thinking on Student Creativity in English Learning: A Mixed Methods Study - Endang Iryani; Suryadi Suryadi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Education in the 21st century requires not only content mastery but also the development of higher-order thinking skills to address complex global challenges. This study investigates the effects of STEM Project-Based Learning (PjBL) and students’ critical thinking on creativity in English language learning. Employing a mixed methods approach with an explanatory sequential design, the study first gathered quantitative data through surveys and tests, followed by qualitative data from interviews and classroom observations. The participants consisted of 200 Grade X students from two senior high schools in Serang City, selected through purposive sampling. The quantitative findings revealed that both STEM PjBL and critical thinking significantly influence student creativity, with strong positive correlations (r = 0.867 and r = 0.889) and moderate effect sizes (Cohen’s d = 0.516 and 0.505). The qualitative data supported these findings, highlighting students’ increased engagement, collaboration, and reflective thinking during project implementation. These results suggest that integrating STEM-based projects in English learning can effectively foster critical and creative thinking skills, offering a promising interdisciplinary approach to language education. The study contributes to current literature by demonstrating the combined impact of PjBL and critical thinking in a language learning context, an area often overlooked in prior research. The findings hold practical implications for curriculum designers and educators seeking to promote 21st-century competencies through integrated, student-centered instruction.